CONTRIBUTIONS OF AMERICAN DESCRIPTIVE LINGUISTIC SCHOOL TO THE STUDY OF VIETNAMESE: A CONTEMPORARY LOOK - Van, Hoang Van (VNU Journal of Foreign Studies, 2020)
This article examines the contributions of the American descriptive linguistic school in the mid-20 th century to the study of Vietnamese. Two most important monographs on Vietnamese grammar by two foremost American descriptivist/structuralist grammarians were taken for examination: Studies in Vietnamese (Annamese) Grammar by Murray B. Emeneau and A Vietnamese Reference Grammar by Laurence C. Thompson. It is clear that among the foreign scholars who have studied Vietnamese, Emeneau and Thompson have made the most substantial contributions to the study of Vietnamese grammar. They both have made a major point in seeking to analyse Vietnamese on the basis of Vietnamese alone, trying to avoid as much as possible any distortion from Indo-European grammatical concepts; and thus have produced good and reliable results. Their descriptive works on Vietnamese are detailed and systematic, meeting most of the criteria of a standard grammar: meticulousness, comprehensiveness, lucidity, rigor, and elegance. Together with the studies of Vietnamese grammar by grammarians of other linguistic traditions, either indigenous or foreign, their works have enriched our ways of looking at language, broadening our understanding of one of the most fruitful approaches to the study of Vietnamese grammar.